Isolation and Characterization of Bacillus spp with Potent Proteolytic and Antipathogenic Activities (Tribhuvan University Journal of Microbiology, 2025)
Objectives: The current study aimed to determine the proteolytic and antipathogenic activity of Bacillus spp isolated from soil samples collected across various ecological and land-use categories in multiple locations within the Kathmandu Valley.Methods: A cross-sectional study was conducted at the Med-Micro Nepal Community Development and Research Centre, Kathmandu. Seventeen different soil samples were collected and processed to isolate Bacillus species. The isolates were identified as Bacillus spp on the basis of their morphological characteristics, Gram's staining, spore staining and biochemical tests based on Bergey's Manual of Systematics of Archaea and Bacteria. The proteolytic activity was screened and determined by well diffusion method on 1% gelatin agar media for both crude and purified form of enzyme. Similarly, antipathogenic assay was done on Mueller Hinton agar by agar well diffusion method.Results: All 17 Bacillus isolates exhibited proteolytic activity, with enhanced activity observed upon partial purification. Notably, isolate AM showed the highest increase (25%) in protease activity, while RS and RH displayed the largest overall proteolytic zones (32 mm and 31 mm, respectively). Isolates RH, RK, FM, FN, and FS demonstrated both strong antipathogenic and proteolytic activities, suggesting a potential correlation between protease production and antimicrobial efficacy.Conclusion: These findings highlight the therapeutic potential of selected proteolytic Bacillus strains, particularly against Streptococcus spp and E. coli.